Virtual Antenna Array-Based Channel Sounding at 300 GHz: Implementation and Field Measurements - Lyu, Yejian; Zhang, Fengchun; Yuan, Zhiqiang; Kyosti, Pekka; Fan, Wei (IEEE antennas and wireless propagation letters, 2024)
Knowledge of spatial profiles of propagation channels holds significant importance in channel modeling, particularly in the subterahertz (sub-THz) frequency band spanning from 100 GHz to 300 GHz. The directional scanning scheme (DSS) offers a straightforward and cost-effective means to achieve such purpose. However, the resulting spatial profiles are subject to the directional characteristics of the employed antenna (e.g., half-power beamwidth and sidelobes). The virtual antenna array (VAA) method, i.e., mechanically relocating a single antenna to specific spatial locations to construct a VAA, can achieve significant enhancement of the spatial resolution and signal-to-noise ratio (SNR) through array signal processing. However, VAA requires phase-coherent measurements among virtual array elements, presenting a challenge to the channel-sounding implementation at sub-THz bands due to the highly sensitive phase at 1 mm level of the wavelength. In our previous work, we introduced a phase-coherent channel sounder capable of stabilizing the phase of the channel-sounding system. Leveraging this technology, we implement and validate the first 300 GHz VAA using an extremely large antenna array setup comprising 1200 array elements in the field measurements in this work. The measured results demonstrated the effectiveness of the VAA scheme, by offering significantly improved SNR and spatial resolution compared with the traditional DSS scheme.